More on Heisenberg's model for high energy nucleon-nucleon scattering - Nastase, Horatiu [UNESP]; Sonnenschein, Jacob (American Physical Society (APS), 2015)
We revisit Heisenberg's model for nucleon-nucleon scattering which admits a saturation of the Froissart bound. We examine its uniqueness, and find that up to certain natural generalizations, it is the only action that saturates the bound. We find that we can extract also subleading behavior for σtot(s) from it, though that requires a knowledge of the wave function solution that is hard to obtain, and a black-disk model allows the calculation of σelastic(s) as well. The wave-function solution is analyzed perturbatively, and its source is interpreted. Generalizations to several mesons, the addition of vector mesons, and curved space regimes are also found. We discuss the relations between Heisenberg's model and holographic models that are dual to QCD-like theories.